High binding site occupancy of corticosteroid-binding globulin by progesterone increases fetal free cortisol concentrations. (August 2020) - Hodyl, Nicolette A.; Stark, Michael J.; Meyer, Emily J.; Lewis, John G.; Torpy, David J.; Nenke, Marni A.
Abstract: Objective: Corticosteroid-binding globulin (CBG) binds and transports cortisol in the circulation in high cortisol-binding affinity (haCBG) and low affinity (laCBG) forms, the latter resulting from enzyme cleavage to target cortisol delivery at sites of inflammation. CBG also has substantial progesterone binding affinity, 3-fold less than cortisol. Progesterone and cortisol are important in the maintenance of pregnancy and in fetal development, respectively. The interactions of cortisol, progesterone and CBG affinity forms have not been studied together. We examined the interaction between progesterone and cortisol with CBG during fetal development. Study design: A retrospective cohort analysis of 351 neonates born between January and December 2012 at the Women's and Children's Hospital, Adelaide, South Australia. Cord blood serum samples were collected immediately following delivery. Clinical data was provided by hospital records. Total cortisol, free cortisol, total progesterone, total CBG and haCBG were measured by immunoassay. Results: Cord blood total and free cortisol, and progesterone concentrations increased with gestational age. Cord blood progesterone concentrations were 100-fold luteal and 10-fold those in late pregnancy maternal circulation. The proportion of haCBG to total CBG was similar to that in healthy non-pregnant adults. However, free cortisol comprised approximately 15% of total cortisol, 3-fold higher than that in adults. Conclusion: In a manner unique to fetal life, very high progesterone concentrations are capable of elevating free cortisol concentrations through competition with cortisol at CBG's hormone binding site, without altered binding affinity through CBG cleavage or altered CBG hormone-binding affinity. High circulating fetal progesterone concentrations compete for CBG binding with cortisol, leading to a 3-fold increase in the free cortisol fraction in cord blood. Higher free-to-bound cortisol may alter fetal cortisol distribution facilitating cortisol's roles such as neurodevelopment in concert with dehydroepiandrosterone (sulfate) and lung maturation, or support cortisol action at times of low ambient cortisol. This mechanism may underlie the known association between cortisol, progesterone and CBG, and be relevant principally in the fetal circulation due to the high progesterone concentrations encountered.